The Effect of Digital Storytelling on Elementary School Students' Reading Literacy: An Experimental Research - Arni Rizkiah; Iik Nurulpaik; Neneng Sri Wulan (Journal of Indonesian Primary School, 2026)
In the digital era, cultivating early reading literacy requires innovative pedagogical approaches that move beyond traditional print-based methods. While digital storytelling has emerged as a promising tool, empirical evidence regarding its specific efficacy in primary school settings remains limited. This study aims to examine the effect of digital storytelling on the reading literacy of elementary school students. Utilizing a quantitative approach with a quasi-experimental design, this research involved 36 students from SD Negeri Kalibuntu, who were divided into an experimental group and a control group. Data on students' reading literacy were systematically gathered using structured observation techniques. The collected data were analyzed using descriptive statistics evaluating individual acquisition scores and classical averages based on a categorization table and inferential parametric statistics via independent and paired-sample t-tests.The findings demonstrated that digital storytelling exerts a highly positive and statistically significant effect on elementary school students' reading literacy. This is evidenced by a substantial increase in the experimental group's average literacy score from a pre-test baseline of 60.17 (low category) to a post-test peak of 92.34 (very high category). Furthermore, the experimental group's post-test literacy score (M = 92.34) significantly outperformed the control group (M = 65.61, low category), with inferential analysis confirming a high statistical significance (p < 0.000). These results indicate that integrating multimedia narratives enhances cognitive engagement and textual comprehension in young learners. Consequently, this study underscores that digital storytelling serves as a potent pedagogical alternative to mitigate low reading literacy, offering critical insights for primary school educators.